Identification of novel GHRHR and GH1 mutations in patients with isolated growth hormone deficiency. (August 2016) - Birla, Shweta; Khadgawat, Rajesh; Jyotsna, Viveka P.; Jain, Vandana; Garg, M.K.; Bhalla, Ashu Seith; Sharma, Arundhati
Abstract: Objective: Human growth is an elementary process which starts at conception and continues through different stages of development under the influence of growth hormone (GH) secreted by the anterior pituitary gland. Variation affecting the production, release and functional activity of GH leads to growth hormone deficiency (GHD), which is of two types: isolated growth hormone deficiency (IGHD) and combined pituitary hormone deficiency (CPHD). IGHD may result from mutations in GH1 and GHRHR while CPHD is associated with defects in transcription factor genes PROP1, POU1F1 and HESX1 . The present study reports on the molecular screening of GHRHR and GH1 in IGHD patients. Methods: A total of 116 clinically diagnosed IGHD patients and 100 controls were enrolled for the study after taking informed consent. Family history was noted and 5 ml blood sample was drawn. Anatomical and/or morphological pituitary gland alterations were studied using magnetic resonance imaging (MRI). DNA from blood samples was processed for screening the GHRHR and GH1 by Sanger sequencing. Results: Mean age at presentation of the 116 patients (67 males and 49 females) was 11.71 ± 3.5 years. Mean height standard deviation score (SDS) and weight SDS were − 4.5 and − 3.5 respectively. Nine (7.8%) were familial and parental consanguinity was present in 21 (19.8%) families. Eighty-three patients underwent MRI and morphological alterations of the pituitary were observed in 39 (46.9%). GH1 and GHRHR screening revealed eleven variations in 24 (21%) patients of which, four were novel deleterious, one novel non-pathogenic and six reported changes. Conclusions: GHRHR contributed more to IGHD in our patients which confirmed that GHRHR should be screened first before GH1 in our population. Identification of GH1 and GHRHR variations helped in defining our mutational spectrum which will play a crucial role in providing predictive and prenatal genetic testing to the patients. Highlights: Higher contribution of GHRHR compared to GH1 mutations in IGHD in our population Identification of novel insertion GHRHR mutation Novel intronic GH1 mutation predicted to be deleterious and affecting the mRNA splicing